On Campus and Off Campus Guide: report on an experience of pedagogical project in Higher Education - Mottin, Lívia Pretto; Aldrovandi, Makeli (BELT - Brazilian English Language Teaching Journal, 2018)
This work aims to present a project of English as an additional language for Brazilian students of mixed levels. Based on the perspective of learning through projects, and considering the need for a meaningful teaching process of additional language, a project was developed to create a guide for exchange students arriving at the university. For the preparation of this guide, 140 students from 5 classes, led by two professors, were mobilized. The guide – the final product of the project – was made available to the International Relations Office of the institution to be distributed to the exchange students who have knowledge in the English language. Working with projects allows all students to be fully involved, offering the group a range of varied and equally important skills and knowledge, making the language lesson more than a time to learn rules about a language, but a moment to exchange knowledge and promote interaction.